KOMUNIKASI PESERTA DIDIK YANG TERISOLIR DAN POPULER DI SMU X KOTA PADANG (Universitas PGRI Sumatera Barat, 2015)
This research aims to describe the characteristics of senior hight school communication isolation and popularity of student. In order to obtain the purpose, qualitative approach was applied. The data of the research were collected by applying such techniques as observation, sociometric, interview, and documentary studies. To check data truthworthiness, trianggulation technique was aplied in wich interview with several classmates of subjects of the reasearch and observation besaid interview and observation were done by co-researcher from the information obtainerd.The result of the research shows shat such isolation and popularity of student in this/her social environtment, aspecially in the school cannot be apart from the result from this dealing with the classmate during classroom communication. Above all, the later has greater responsibility for the subject’s internal condition in responding his social environtment